Risk factors for long term complications among patients of endocrine clinic in Hospital Penang, Malaysia - Wasif Gillani; Syed Sulaiman; Shameni Sundram; Maisharah Sheikh Ghadzi; Noor Haroon; Nur Hafzan Md Hanafiah (Journal of Health Sciences, 2012)
Introduction: The prevalence of diabetes is on the increase and an estimated 239 million people worldwide are expected to have the condition by the year 2020 (1). Diabetes mellitus (DM) represents a serious health care challenge. The aim of the study was to evaluate the patient clinical characteristics and risk factors for long term complications in the endocrine clinic of Hospital Penang, Malaysia. Methods: Descriptive Prospective cross-sectional study design was chosen. To achieve a power of 0.7 with alpha set at 0.05, 186 subjects were required for the study but researcher increase the sample to 297 in case of drop out. Self-developed data collection form was used to collect the patient information. Results: 297 (100%) patients were enrolled from OPD diabetic clinic of Hospital Palau Pinang. Among the sample 150 (50.5%) were males and rest 147 (49.5%) females. Malay males mean weight at the time of diagnosis significantly higher (p<0.001,) as compared to other ethnics, same results found among Malay females (p<0.001). Findings suggested increased number of risk factors among the study population. Finding also showed that hypertension found among all the classes of diagnosis. Signifi cant variable are diagnosis class and medication consideration. Conclusion of the study suggested that majority of patients are at high risk of long-term complications and comorbidies. It has been found that increased rate of risk factors have been found among the study population and non-significant to sociodemographic differences.